Pi might look random but it’s full of hidden patterns - Humble, Steven (New Zealand Science Review, 2015)
The following article is republished from The Conversation, dated March 14, 2016. The article has not been edited, and we have attributed the authors and their institutes, and given the internet citations. The Conversation, March 14, 2016. https://theconversation.com/pi-might-look-random-but-its-full-of-hidden-patterns-55994